2021
DOI: 10.1016/j.algal.2021.102360
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ohmic heating in the composition of extracts from Gracilaria vermiculophylla

Abstract: Electric field-based technologies for extraction processes have been gaining importance due to sustainability concerns. This work aims to assess the potential of ohmic heating as an efficient and feasible tool for the extraction of different biocompounds from Gracilaria vermiculophylla and its effect on the extracts' composition. Different ratios of water/ethanol (0 to 75% ethanol, v/v) were used to target different families of biocompounds. The ohmic heating-based extraction was performed at 82 • C under elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…The DPPH free radical, ABTS, hydroxyl radical, and superoxide radical scavenging activities of the obtained polysaccharides by Sevag method were better than that by trichloroacetic acid method. Pereira et al (2021) separated several compounds based on the principle that mixtures of water and ethanol with different proportions have different affinities to different compounds, and found that 100% water was the best solvent for carbohydrates. Andriamanantoanina et al (2007) obtained homogeneous polysaccharides by sequential extraction method and found that only the polysaccharides extracted by water/ethanol = 60% had low gelling.…”
Section: E X Tr Ac Ti On S Epar Ati On and Purifi C Ati On Of G Sa Smentioning
confidence: 99%
“…The DPPH free radical, ABTS, hydroxyl radical, and superoxide radical scavenging activities of the obtained polysaccharides by Sevag method were better than that by trichloroacetic acid method. Pereira et al (2021) separated several compounds based on the principle that mixtures of water and ethanol with different proportions have different affinities to different compounds, and found that 100% water was the best solvent for carbohydrates. Andriamanantoanina et al (2007) obtained homogeneous polysaccharides by sequential extraction method and found that only the polysaccharides extracted by water/ethanol = 60% had low gelling.…”
Section: E X Tr Ac Ti On S Epar Ati On and Purifi C Ati On Of G Sa Smentioning
confidence: 99%
“…Its applications include the food, pharmaceutical, cosmetic, biotechnological, and biomedical sectors, presenting a notable market size valued at 264 million USD in 2022 [ 10 ]. Agar is mainly composed of agarose and agaropectin, the former being the gel-forming component, with a linear chain of repeating units of (1,3)-linked-β-D-galactose and (1,4)-linked-3,6-anhydro-α-L-galactose [ 11 ]. The gelling ability of agar is hindered by the substitution of the hydroxyl groups of l-galactose by sulphate esters, methyl ethers, or pyruvate acid ketals.…”
Section: Introductionmentioning
confidence: 99%
“…However, these multi-step methods are time-, energy-, water-, and solvent-consuming, generating large amounts of wastewater. Therefore, the search for alternative polysaccharide extraction methods that are eco-friendlier, due to the absence of a strong alkali, and predictably cheaper, as fewer steps are included in the extraction process, has boosted over increasing ecological concerns [ 11 , 13 ]. These include microwave-, ultrasound-, and enzyme-assisted extraction, which are relatively environment-friendly technologies but still rather limited to the laboratory scale [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate these challenges, several studies have been conducted in recent years on the extraction of bioactive compounds from seaweeds using emerging technologies (Getachew et al, 2020). These technologies include microwave-assisted extraction (Charoensiddhi et al, 2015), ultrasound-assisted extraction (Moreira et al, 2017), pulsed electric field assisted extraction (Robin et al, 2018), ohmic heating (Pereira et al, 2021), deep eutectic and natural deep eutectic solvents (Das et al, 2016;Obluchinskaya et al, 2019), supercritical carbon dioxide extraction (Saravana et al, 2017), and subcritical water (pressurized liquid extraction) (Sumampouw et al, 2021). Among these extraction technologies, extraction with sub and supercritical fluids is getting increasing attention.…”
Section: Introductionmentioning
confidence: 99%